1984
DOI: 10.1073/pnas.81.5.1594
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and binding constants for acetylcholine derived from the falling phase of miniature endplate currents.

Abstract: In previous papers we studied the rising phase of a miniature endplate current (MEPC) to derive diffusion and forward rate constants controlling acetylcholine (AcCho) in the intact neuromuscular junction. The present study derives similar values (but with smaller error ranges) for these constants by including experimental results from the fallins phase of the MEPC. We find diffusion to be 4 x 10-6 cm2 slightly slower than free diffusion, forward binding to be 3.3 x 107 M-s-, and the distance from an average re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 30 publications
9
80
0
1
Order By: Relevance
“…One might imagine that the BL would block movement of acetylcholine across the synaptic cleft, but kinetic studies show that its diffusion to receptors is unimpeded (32). This result is consistent with conclusions reached from analysis of glomerular BL in kidney, which is an effective filter only for macromolecules (33).…”
Section: Neuromuscular Transmissionsupporting
confidence: 79%
“…One might imagine that the BL would block movement of acetylcholine across the synaptic cleft, but kinetic studies show that its diffusion to receptors is unimpeded (32). This result is consistent with conclusions reached from analysis of glomerular BL in kidney, which is an effective filter only for macromolecules (33).…”
Section: Neuromuscular Transmissionsupporting
confidence: 79%
“…4 and one corresponding to the limiting case where all ACh molecules were released instantly. D for ACh within the synaptic cleft was about 2-fold smaller than DACh, consistent with impeded movement through basal lamina material (19).…”
mentioning
confidence: 80%
“…Of the many models that have been proposed to simulate synaptic currents (Magleby & Stevens, 1972a;Gage, 1976;Steinbach & Stevens, 1976;Rosenberry, 1979;Wathey, Nass & Lester, 1979;Land, Salpeter & Salpeter, 1980, 1981Land, Harris, Salpeter & Salpeter, 1984;Madsen, Edeson, Lamtt & Milne, 1984;Madsen, Edeson & Milne, 1987), those presented by Land et al (1981Land et al ( , 1984 and Wathey et al (1979) are of particular relevance to the present work, since, in these models, receptor density was one of the parameters explicitly examined. Thus, for example, Land et al (1981) concluded that, when the esterase is blocked, no correlation between miniature endplate current (MEPC) amplitude and rise time is to be expected if receptor density is high, while a positive correlation is anticipated if the density is reduced.…”
Section: Methodsmentioning
confidence: 99%
“…This prediction was borne out by their experimental results, using a-bungarotoxin to reduce the effective concentration of ACh receptors (Land et al 1981). In addition, both Land et al (1984) and Wathey et al (1979) (Sakmann, 1978;Jackson, Wong, Morris, Lecar & Christian, 1983 …”
Section: Methodsmentioning
confidence: 99%